Tail in the duodenum - Ranganathan, Sruthi; Mohanapriya, T.; Singh, K. Balaji (International Surgery Journal, 2018)
Inflammatory myofibroblastic tumour, commonly called as pseudotumor is a soft tissue tumour, commonly occurring in children and young adults and very rarely in elderly. Lungs are the most commonly affected site but sometimes it can occur in retroperitoneum and abdominal cavity. It contains spindle cells, myofibroblasts, lymphoctyes, plasma cells, and histiocytes. It is a non-encapsulated lesion. The pathogenesis of IMT remains unclear, although various allergic, immunogenic infectious mechanisms have been postulated. They are locally recurrent (15-37%) and rarely metastasize (<5%). IMT features mimcs malignancy on UGIscopy and radiological imaging and hence surgical exploration and complete resection is required for diagnosis and treatment. The worldwide incidence of IMT is 0.04- 0.7%. Here is a case of inflammatory myofibroblastic tumour in duodenum presented with complaints of vomiting and melena.